Bending-resistant flexible cable and cable manufacturing method
By adjusting the manufacturing process of composite materials and adding fire-resistant fillers, the bending performance and flame retardancy of flexible cables are improved, and the insufficient performance of flexible cables in mechanical impact and fire is solved, and good insulation and safety are achieved.
Patent Information
- Application Number
- CN202411319064.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-21
- Publication Date
- 2024-12-13
AI Technical Summary
Existing flexible cables are prone to damage under mechanical external impact, and their bending resistance is insufficient, which limits their wide application in the field of automation.
By changing the ratio of mica scales to powder, grinding time, and ultrasonic fiber suspension during the manufacturing process of composite aramid mica paper, combining the ratio of crosslinked polyethylene powder to PDMS, nitrogen-based flame retardant and phytic acid When using zinc, composite insulation materials are manufactured by spinning, and extruded fire-resistant filler and rolled copper sheath are added to the outer layer to improve the bending performance and flame retardancy of the cable.
It realizes that the flexible cable has a long breakdown time at high voltage, an appropriate bending radius, a qualified flame retardant test, good fire resistance, and a halogen-free characteristic meets the requirements, improving the overall performance and safety of the cable.
Smart Images

Figure CN119132740A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a bending-resistant flexible cable and a method for manufacturing the cable. Background Art
[0002] Rigid mineral insulated cables have good flame retardancy, but poor flexibility and cannot meet special usage requirements. Flexible cables are cables that can be bent, shaped and folded, and are widely used in industrial electronic systems, automatic production lines, storage equipment, robots, metallurgical industry, machine tools and other automation fields.
[0003] During use, flexible cables need to maintain good bending performance and tensile strength to ensure their normal use. In addition, flexible cables need to have a certain strength to prevent heavy objects from falling on the cables and causing insulation breakdown, thereby affecting their normal use and even causing safety and quality accidents. Good flame retardancy and fire resistance allow flexible cables to maintain normal power supply and transmission functions in fires, while reducing the amount of smoke generated during the combustion of cable materials. It is crucial to manufacture flexible cables with good comprehensive performance.
[0004] The quality of the insulating material in the flexible cable affects the insulation of the cable. Poor insulation of the material will cause the cable to be easily punctured during use. Patent CN117820747B discloses "a cross-linked polyethylene-based flexible cable insulation layer material and its preparation method". The invention creatively adds modified montmorillonite and modified glass microbeads, and combines them with cross-linked polyethylene and various components to prepare a flexible cable insulation layer material. The insulation material has good mechanical properties and high thermal conductivity.
[0005] The outermost layer of traditional flexible cables is usually made of cross-linked polyethylene sheath or other organic materials. For example, patent CN106977778B discloses a "method for preparing a flexible cable sheath material", which is prepared from a variety of raw materials such as natural rubber, silicone rubber, ethyl acetate, plasticizer and antioxidant. It has high flexibility, good tensile properties, good insulation and good solvent corrosion resistance. However, the fire resistance is poor, and its components are complex and poorly fused. Long-term use will cause the sheath to crack. Using metal as the sheath of the cable will reduce the flexibility of the cable and increase its rigidity.
[0006] When a disaster occurs, the large amount of smoke generated by the cable will make it difficult for people to escape and cause secondary damage to the human body. Patent CN116285320B discloses "a low-voltage flexible cable". The cable made of main resin, benzoxazine, aluminum hydroxide, 3-(2,5-diaminophenyl)-1-propanol and other raw materials has good flame retardancy and low smoke density.
[0007] In order to make the cable surface able to withstand greater mechanical external force impact, most cables on the market use metal materials such as steel strips, steel wires, aluminum strips, and aluminum wires as cable armor protection layers, which solves the problem of cable damage caused by mechanical external force impact on the cable surface. However, it is well known that the protective layers used in these process methods make it impossible for the cables to maintain good bending resistance, limiting their wide application. Therefore, it is crucial to ensure that the cables have good comprehensive performance and good bending resistance.
[0008] Therefore, a bending-resistant flexible cable and a method for manufacturing the cable are proposed. Summary of the invention
[0009] The object of the present invention is to provide a bending-resistant flexible cable and a method for manufacturing the cable. By changing the ratio of muscovite flakes to muscovite powder, grinding time, and the amount of ultrasonic fiber suspension in suspensions one and two in the manufacturing process of two-layer composite aramid mica paper, the obtained bending-resistant flexible cable has good bending performance and a long breakdown time at rated voltage. By changing the ultrasonic time, the type of diisocyanate, the raw material ratio of the mixture and the pressing temperature in the composite insulating material manufacturing method, the bending performance of the cable is good. By changing the ratio of cross-linked polyethylene powder and PDMS, the type and amount of nitrogen flame retardant, and the amount of zinc phytate and hexagonal boron nitride, the flame retardant test results of the flexible cable obtained by spinning are qualified, the smoke emission is small, and the bending performance is general. By changing the amount of aluminum hydroxide in the extruded fireproof filler and the particle size of the raw material, the flexible cable is qualified in the fire resistance test and meets the halogen-free characteristic requirements. By changing the type of raw materials of each layer, the obtained flexible cable has good bending performance.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] In one aspect, the present invention provides a method for manufacturing a bending-resistant flexible cable, comprising the following steps:
[0012] The fibrillation suspension is ultrasonically treated for 15-25 minutes to obtain an ultrasonic fibrillation suspension; muscovite flakes and muscovite powder are mixed with water at a ratio of 1-23:1-3 in parts, and ground for 13-20 minutes to obtain muscovite slurry; 0-10 parts of diisocyanate are added to the muscovite slurry to react to obtain modified muscovite slurry; 8-10 parts of the ultrasonic fibrillation suspension and the modified muscovite slurry are mixed and formed to obtain an aramid mica paper intermediate; coconut oil primary amine and silane epoxy resin are mixed at a ratio of 0.01-0.03:1 to obtain a mixture; the mixture is applied to the aramid mica paper intermediate to obtain a coating layer one; 0-50 parts of the ultrasonic fibrillation suspension and the modified muscovite slurry are mixed and formed, and then laminated with the aramid mica paper intermediate and the coating layer one to obtain two layers of composite aramid mica paper;
[0013] Mica paper-based insulation material has good insulation performance, but its strength is low, and it needs to add reinforcing materials to improve its overall mechanical strength, dielectric strength, reinforcing effect and other functions. The present invention uses aramid meta-precipitated fiber materials for reinforcement. Muscovite flakes have the same main components as muscovite powder, but the particle size is not uniform. After grinding, the mica particle size in the muscovite slurry is relatively uniform, and a small amount of muscovite powder is used to reduce the cost of the material.
[0014] The coating layer 2, the composite glass cloth and the two layers of composite aramid mica paper are laminated at 105-115° C. to obtain a composite insulating material; the coating thickness of the coating layer 1 and the coating layer 2 are both 0-30 μm;
[0015] Glass cloth has good insulation properties and has a good protective effect on the conductors in the cable. It also has strong hardness, which is beneficial to enhance the mechanical strength of the cable. Glass cloth is soaked with diisocyanate to obtain composite glass cloth.
[0016] Aramid meta-fiber is a hydrophobic material with a smooth surface. Ultrasonic treatment improves the dispersion of aramid fiber in the suspension on the one hand, and improves its surface roughness on the other hand. Excessive diisocyanate is added to the modified muscovite slurry. During the subsequent heating and lamination process, the diisocyanate reacts with the hydroxyl groups on the muscovite surface, and the coconut oil primary amine attacks the epoxy group of the silane epoxy resin to form a hydrogen bond. The excess diisocyanate then reacts with the open-ring silane epoxy resin to improve the compatibility between the interfaces. The adhesion between the aramid fiber and the silane epoxy resin after ultrasonic treatment increases.
[0017] The addition of silane epoxy resin not only improves the compatibility between the components, but also has the function of waterproofing and moisture-proofing, and also increases the bending resistance of the flexible cable.
[0018] Cross-linked polyethylene powder and PDMS are mixed at a ratio of 1-3:9-97 to obtain a suspension; 0-4.5 parts of a nitrogen flame retardant, 0-4 parts of zinc phytate and 1-2 parts of hexagonal boron nitride are added to the suspension, stirred and mixed, and ultrasonicated to obtain a spinning solution; the spinning solution is spun to obtain a fireproof material;
[0019] Mixing magnesium hydroxide, 11-20 parts of aluminum hydroxide and PDMS, and grinding to an average particle size of 230-400 nm to obtain an extruded fireproof filler;
[0020] The bending-resistant flexible cable is manufactured by using the conductor material, the composite insulating material, the glass fiber, the fireproof material, the metal layer and the sheath.
[0021] Preferably, the amount of ultrasonic fiber precipitation suspension in the second suspension is 30-50 parts.
[0022] Preferably, the diisocyanate is one of isophorone diisocyanate, 2,4-diisocyanate-1-methylcyclohexane, 1-isocyanato-2-(3-isocyanatopropyl)cyclohexane and 4-isocyanate-2-[(2-isocyanatecyclohexyl)methyl]-1-methylcyclohexane; and the amount of the diisocyanate used is 10 parts.
[0023] Preferably, the coating thickness of the coating layer 1 and the coating layer 2 are both 10-30 μm.
[0024] Preferably, the nitrogen-based flame retardant is one or two of N-cyano-N'-(hydroxymethyl)guanidine, a polymer of cyanoguanidine and N-(2-aminoethyl)-1,2-ethylenediamine, melamine, dicyandiamide and dodecylguanidine hydrochloride.
[0025] Preferably, the amount of the nitrogen-based flame retardant is 3-4.5 parts; the amount of the zinc phytate is 3-4 parts.
[0026] In addition to its flame retardant effect, zinc phytate also provides a good antioxidant effect for flexible cables. Nitrogen flame retardants form a composite protective layer of nitrogen and carbon layers under high temperature conditions. At the same time, the non-flammable gas generated dilutes the flammable hexagonal boron nitride. Mixed with the first two, as a composite flame retardant, it improves the flame retardant effect of flexible cables. Cross-linked polyethylene is used in conjunction with flame retardants to achieve the effect of less smoke under combustion conditions.
[0027] Preferably, the conductor material is one of a non-compacted annealed copper conductor, a compacted annealed copper conductor and a non-compacted copper conductor.
[0028] Compared with non-compacted copper conductors, the non-compacted copper annealed copper conductor changes the crystal phase arrangement of the metal during the annealing process through heating and subsequent cooling, thereby reducing the hardness of the copper rod and increasing its flexibility, thereby improving the bending resistance of the bending-resistant flexible cable. The bending properties of flexible cables made of non-compacted annealed copper conductors and compacted annealed copper conductors are similar, but the preparation process of compacted annealed copper conductors is complicated, which is not conducive to simplifying the process.
[0029] Preferably, the conductor material is coated with the composite insulating material; the glass fiber is filled outside the composite insulating material to obtain an insulating layer; the outside of the insulating layer is tightly wrapped with the fireproof material to obtain a fire-retardant belt; the outside of the fire-retardant belt is wrapped with the metal layer to obtain a metal belt; the extruded fireproof filler is filled; the sheath is used as the outermost layer to obtain the bending-resistant flexible cable;
[0030] In a fire situation, mica is prone to fall off when used alone. Using it in combination with aramid fiber and a mixture containing silane epoxy resin reduces the probability of mica falling off, thereby ensuring the insulation of the cable in a fire state and ensuring the safety of the cable. Glass fiber not only has a toughening effect, but also has flame retardancy, which can effectively prevent flames from affecting the system. The metal hydroxide in the extruded fireproof filler has been reasonably compounded to achieve good fire resistance at high temperatures.
[0031] The metal layer is one of TU2H01 copper strip for interlocking armor, H65H02 copper strip for interlocking armor, argon arc welding copper strip, resistance welding copper strip, aluminum alloy strip for interlocking armor and cold press welding copper strip.
[0032] Resistance welding melts the copper strip during the welding process and pressurizes the copper material to tightly bond it, preserving the original bendability and flexibility of the copper material to the greatest extent. Cold-pressed copper strips break the oxide film on the contact surface of the workpiece under high pressure, allowing the oxide films squeezed out of the two workpiece surfaces to fuse and penetrate into the interior of the two workpieces, thereby achieving the purpose of welding. However, the bendability and flexibility of cold-pressed copper strips are lower than those of resistance welding copper strips, and cold-pressed copper strips have higher requirements for workpieces.
[0033] Argon arc welding uses non-consumable electrodes and argon shielding gas to perform welding work, which can effectively prevent the oxidation of copper materials. In addition, high current is used to form a liquid molten pool on the copper metal being welded. The liquid molten pool is metallurgically bonded with copper, which minimizes deformation during the welding process. Therefore, the welding material has good bending properties.
[0034] Preferably, the sheath is one of corrugated copper and WDZN-BYJ type low-smoke halogen-free sheath.
[0035] On the other hand, the present invention provides a bending-resistant flexible cable, characterized in that: the bending-resistant flexible cable comprises a conductor material, a composite insulating material, glass fiber, a fireproof material, a metal layer, an extruded fireproof filler and a sheath; the bending-resistant flexible cable is manufactured by any of the manufacturing methods described above; by changing the manufacturing method of the two-layer composite aramid mica paper, the breakdown time of the bending-resistant flexible cable is 14-20min, and the bending radius is 12.6R-19.4R; by changing the manufacturing method of the composite insulating material, the bending radius of the bending-resistant flexible cable is 13.8 R-19.5R; the manufacturing method of the fireproof material is changed, the flame retardant test result of the bending-resistant flexible cable is qualified, the minimum light transmittance is 60.3%-70.5%, and the bending radius is 16.7R-19.8R; the manufacturing method of the extruded fireproof filler is changed, the fire resistance test result of the bending-resistant flexible cable is qualified, the pH weighted value is 4.4-4.7, and the conductivity weighted value is 7.8-9.8μs / mm; the types of the conductor material, the metal layer and the sheath are changed, and the bending radius of the bending-resistant flexible cable is 11.5R-17.6R.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The present invention changes the ratio of the amount of ultrasonic fiber precipitation suspension and modified muscovite slurry between different layers, and then compounds the layers to obtain two layers of composite aramid mica paper, and the aramid fiber is filled in the gaps of the muscovite component. The double layers of muscovite slurry and aramid fiber with different ratios are compounded, so that the insulating material provides better insulation and bending resistance for the flexible cable.
[0038] 2. By modifying the surface of the aramid fiber and muscovite mica in the aramid mica paper, soaking the glass cloth, and then laminating them layer by layer, the interface compatibility between the aramid mica paper and the glass cloth is improved, thereby ensuring the insulation of the material while also giving the insulation material excellent mechanical properties.
[0039] 3. The fireproof material produced by cross-linking polyethylene powder and PDMS to form a suspension, then adding organic nitrogen flame retardant, zinc phytate and hexagonal boron nitride to form a spinning solution, and using a twin-screw extruder to spin and manufacture is beneficial to improving the bending resistance of the flexible cable. At the same time, it also ensures that the flexible cable has a flame retardant effect, less smoke is generated when a fire occurs, and the escape rate is high.
[0040] 4. By using magnesium hydroxide and aluminum hydroxide together and adding silane, under high temperature burning conditions, magnesium hydroxide and aluminum hydroxide form magnesium oxide and aluminum oxide, which prevents the further occurrence of combustion reaction and has good fire resistance. The particle size of the fireproof filler is reduced, so that it has a larger specific surface area, which has good fire resistance on the one hand, and on the other hand, it also gradually reduces the weighted value of the conductivity of the flexible cable, and has good conductivity.
[0041] 5. The outer layer of traditional flexible cables usually uses a low-smoke halogen-free sheath as a protective layer. Compared with metallic copper, the polyolefin material in the low-smoke halogen-free sheath is an organic material with lower melting point and fire resistance than metallic copper, and a large amount of smoke will be generated during the combustion process, causing toxic gas pollution, thereby causing secondary damage to the body. However, the use of metallic copper will reduce the bending performance of the cable. The use of corrugated copper sheath improves the bending resistance of the flexible cable. In addition, the corrugated copper sheath constitutes the first physical line of defense to protect the internal structure from being damaged. In addition, by changing the type of conductor material, metal layer and sheath, the resulting bending-resistant flexible cable has good bending resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a graph showing the bending performance test results of the bending-resistant flexible cable of Example 26 of the present invention;
[0043] Figure 2 It is a structural diagram of the bending-resistant flexible cable of the present invention.
[0044] The numbers in the figure represent: 1-conductor material, 2-composite insulating material, 3-glass fiber, 4-fireproof material, 5-metal layer, 6-extruded fireproof filler, 7-sheath. DETAILED DESCRIPTION
[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] See also Figure 1 to Figure 2 The present invention provides a bending-resistant flexible cable and a method for manufacturing the cable, and the technical solution is as follows:
[0047] The substance information involved in the present invention is as follows:
[0048] Polydimethylsiloxane (PDMS) CAS: 107-46-0; Isophorone diisocyanate CAS: 4098-71-9; 2,4-diisocyanato-1-methylcyclohexane CAS: 10581-16-5; 1-isocyanato-2-(3-isocyanatopropyl)cyclohexane CAS: 22458-63-5; 4-isocyanato-2-[(2-isocyanatocyclohexyl)methyl]-1-methylcyclohexane CAS: 94213-2 8-2; N-cyano-N'-(hydroxymethyl)guanidine (Nnge) CAS: 13101-26-3; polymer of cyanoguanidine and N-(2-aminoethyl)-1,2-ethylenediamine (Dde-Dte) CAS: 50862-68-5; melamine (Mme) CAS: 108-78-1; dicyandiamide (Dme) CAS: 461-58-5; dodecylguanidine hydrochloride (Dhe) CAS: 13590-97-1.
[0049] Example 1
[0050] Aramid meta-fibrillation was dispersed in deionized water to obtain a 10% by mass fibrillation suspension; the fibrillation suspension was ultrasonicated at a power of 500 W for 10 min to obtain an ultrasonic fibrillation suspension; muscovite flakes and muscovite powder were mixed with water at a ratio of 9:1 to obtain a muscovite suspension; the mass fraction of muscovite flakes and muscovite powder in water in the muscovite suspension was 10%; the muscovite suspension was put into a grinding tank, the ball-to-material ratio was controlled to be 4:1, and the ratio of small and medium balls was 1:1, The grinding speed was set to 300 rpm and the grinding time was set to 15 min to obtain muscovite slurry; 200 parts of muscovite slurry were heated to 90°C, 10 parts of diisocyanate and 3 parts of sodium dodecyl sulfate were added thereto under stirring, and 0.03 parts of azobisisobutyronitrile were added thereto, and the modified muscovite slurry was obtained after reacting for 2 h; 10 parts of ultrasonic fiber precipitation suspension and 90 parts of modified muscovite slurry were mixed evenly, and suspension 1 was obtained by ultrasonication at a power of 500 W for 20 min; the ultrasonic fiber precipitation suspension in suspension 1 was The total number of parts of the suspension and the modified muscovite slurry is 100 parts; the suspension is placed on a net to be shaped, and an aramid mica paper intermediate is obtained after the shaping; the aramid mica paper intermediate is transferred to the mesh for standby use, and then coconut oil primary amine and silane epoxy resin are mixed in a ratio of 0.01:1 to obtain a mixture, and then coated on the aramid mica paper intermediate to obtain a coating layer; the coating layer and the aramid mica paper intermediate constitute aramid mica paper; 50 parts of the ultrasonic precipitation fiber suspension and 50 parts of the modified muscovite slurry are mixed evenly. The suspension was homogenized, and ultrasonicated for 20 minutes at a power of 500 W to obtain a second suspension; the total number of parts of the ultrasonic precipitation fiber suspension and the modified muscovite mica slurry in the second suspension was 100 parts; the second suspension was formed on a net to obtain an aramid mica paper second intermediate; then the aramid mica paper second intermediate was transferred to the aramid mica paper first to obtain the aramid mica paper second; the aramid mica paper second was laminated, and then pressed at 0.4 MPa for 5 minutes, and finally dried at 105°C for 10 minutes to obtain a two-layer composite aramid mica paper;
[0051] The glass cloth is immersed in diisocyanate for 5 hours, and then the glass cloth is taken out and dried to obtain a composite glass cloth; the composite glass cloth is coated with the mixture of 0.1 mm to obtain a coating layer 2; then it is laminated with two layers of composite aramid mica paper, the pressing temperature is 105°C, the pressing pressure is 0.5 MPa, the pressing time is 5 minutes, and finally it is dried at 105°C for 5 minutes to obtain a composite insulating material; the coating thickness of the coating layer 1 and the coating layer 2 are both 10 μm;
[0052] The cross-linked polyethylene powder and PDMS are mixed to obtain a suspension; wherein the ratio of the cross-linked polyethylene powder to the PDMS is 3:22; 3 parts of nitrogen flame retardant, 4 parts of zinc phytate and 1 part of hexagonal boron nitride are added to 92 parts of the suspension, stirred and mixed for 2.5 hours, and ultrasonicated for 1 hour to obtain a spinning solution; the ratio of the two components in the nitrogen flame retardant is 1:1; the total amount of the suspension, nitrogen flame retardant, zinc phytate and hexagonal boron nitride is 100 parts; the spinning solution is placed in a twin-screw extruder for spinning The spinning temperature range of the first zone is 115-150°C, the spinning temperature range of the second zone is 150-250°C, and the spinning temperature range of the third zone is 250-270°C, and spun fibers are formed by extrusion; after the spun fibers are cooled, they are stretched to 3 times their own length to obtain stretched spun fibers; the stretched spun fibers are extracted in a tetralin solvent, the extraction soaking time is 30 minutes, and then taken out and air-dried, and repeatedly washed with deionized water, dried, and woven to obtain a fireproof material;
[0053] A non-compacted annealed copper conductor is used as a conductor material, and a composite insulating material is used to wrap the conductor material; then, glass fiber is filled outside the composite insulating material to obtain an insulating layer; the outside of the insulating layer is tightly wrapped with a fireproof material to obtain a fire-retardant belt; the outside of the fire-retardant belt is wrapped with an alloy layer (aluminum alloy belt for interlocking armor); then, an extruded fire-retardant filler made of magnesium hydroxide and PDMS is filled in a ratio of 6:11; the outermost layer uses a corrugated copper tube sheath as a protective layer to obtain a bending-resistant flexible cable.
[0054] Example 2-12
[0055] Different from Example 1, the following preparation conditions are changed, as shown in Table 1.
[0056] Table 1 Changes in conditions during the manufacturing process of two-layer composite aramid mica paper
[0057]
[0058] Embodiment 13
[0059] The bending-resistant flexible cables prepared in Examples 1-12 and Comparative Examples 1 and 2 were subjected to performance tests, including bending performance and insulation. The test was conducted in accordance with the method of GB / T 3048-2007 "Test Methods for Electrical Performance of Wires and Cables". The insulation was tested by testing the breakdown time of the bending-resistant flexible cables under AC3.5kV conditions, and checking the appearance of the bending-resistant flexible cables after the bending test (12D), and the final bending performance and breakdown time results were recorded in Table 2. The bending radius is expressed as a multiple of the outer diameter of the cable, and the outer diameter of the cable is recorded as R.
[0060] Table 2 Test results of bending performance and insulation of bending-resistant flexible cables
[0061] Group Breakdown time (min) Bending radius Example 1 20 17.5R Example 2 21 18.3R Example 3 20 18.0R Example 4 18 15.8R Example 5 17 15.4R Example 6 22 18.6R Example 7 21 17.5R Example 8 20 17.2R Example 9 20 16.7R Example 10 19 16.0R Embodiment 11 17 14.7R Example 12 16 14.0R Comparative Example 1 16 19.4R Comparative Example 2 14 12.6R
[0062] The insulation of a material is usually expressed in terms of dielectric strength, which is a measure of the insulation strength of a material. The greater the maximum voltage that a cable can withstand per unit thickness when it is broken down, the better the insulation effect of the cable. At the same voltage, the longer the time the cable is broken down, the better the insulation effect. The smaller the bending radius of a bending-resistant flexible cable is than the multiple of the outer diameter of the cable, the better its bending performance is, and vice versa, the bending performance is reduced. The breakdown time of the bending-resistant flexible cable prepared by the present invention is 14-20min, and the relevant technical requirements are that the cable is not broken down within 15min under the corresponding voltage. Except for comparative example 2, the present invention has a long breakdown time and meets the requirements, indicating that the prepared bending-resistant flexible cable has good insulation. The bending radius of the cable is 12.6R-19.4R, which has better bending properties than traditional rigid cables. Comparative examples 1 and 2 respectively reduce the amount of muscovite flakes and the ultrasonic precipitation fiber suspension in suspension 2, and the breakdown time of the flexible cable meets the test requirements, but the bending performance is reduced; the insulation of the flexible cable in comparative example 2 is poor, but the bending radius is relatively reduced. The stability and durability of the bending-resistant flexible cable during construction and use are guaranteed.
[0063] Examples 14-22
[0064] Different from Example 1, the process of the following manufacturing method is changed, as shown in Table 3.
[0065] Table 3 Composite insulation material manufacturing method information
[0066]
[0067]
[0068] Embodiment 23-25
[0069] Different from Example 14, the coating thicknesses of coating layer 1 and coating layer 2 are 15 μm, 20 μm and 30 μm respectively.
[0070] Comparative Example 3
[0071] The difference from Example 14 is that the amount of diisocyanate used is 0 part.
[0072] Comparative Example 4
[0073] Different from Example 14, the mixture of coconut oil primary amine and silane epoxy resin is not coated, and the aramid mica paper first intermediate, the aramid mica paper second intermediate and the composite glass cloth are directly laminated to manufacture the composite insulating material.
[0074] Embodiment 26
[0075] The bending performance test of the bending-resistant flexible cables manufactured in Examples 14-25 and Comparative Examples 3 and 4 was carried out, and the test method was carried out in accordance with the test method of Example 13. The final test results are as follows: Figure 1 shown.
[0076] The bending performance test results of the bending-resistant flexible cable prepared by the present invention show that its bending radius is 13.8R-19.5R, and the bending resistance is good. By extending the ultrasonic time of the aramid meta-precipitated fiber, the bending radius is reduced. In Examples 16-19, by changing the type of diisocyanate for surface modification of muscovite, the bending performance of the flexible cable is changed, and the bending radius is in the range of 14.0R-16.7R. Example 20 changes the amount of the catalyst coconut oil primary amine, and the bending resistance of the flexible cable is changed. In Examples 20-22, by increasing the pressing time, the bending radius first decreases and then increases, and the overall trend is reduced. The test results of Examples 14, 23-25 show that with the increase of the coating thickness, the bending radius shows a trend of decreasing and increasing. Under the manufacturing method of Example 24, the bending radius reaches the lowest and the bending performance is the best. In Comparative Examples 3 and 4, no diisocyanate or mixture is added, and the bending resistance of the cable decreases.
[0077] Examples 27-37
[0078] The manufacturing method of the fireproof material is changed compared with Example 1, as shown in Table 4.
[0079] Table 4 Manufacturing method of fireproof material
[0080]
[0081] Comparative Example 7
[0082] Different from Example 31, the nitrogen-based flame retardant is only Mme.
[0083] Comparative Example 8
[0084] Different from Example 31, the nitrogen-based flame retardant is only Nnge.
[0085] Comparative Example 9
[0086] Different from Example 31, only an equal amount of cross-linked polyethylene powder was used as the fireproofing material.
[0087] Embodiment 38
[0088] The bend-resistant flexible cables obtained according to the manufacturing methods of Examples 27-37 and Comparative Examples 5-9 were tested for flame retardancy, low smoke and bending resistance. The test method for bending resistance is carried out with reference to Example 13. The flame retardant performance test is carried out with reference to GB / T18380.3-2001 "Combustion test of cables under flame conditions Part 3: Combustion test method for bundled wires or cables"; the test pass index is that the length of carbonization on the sample should not exceed 2.5m upward from the bottom edge of the nozzle. The low smoke characteristics of the flexible cable are determined according to GB / T17651.1-2021 "Determination of smoke density of cables or optical cables burning under specific conditions", and the minimum light transmittance is used to characterize the low smoke performance of the cable. The higher the minimum light transmittance, the better the low smoke performance. The final test results are shown in Table 5.
[0089] Table 5 Flame retardant, low smoke and bending resistance test results
[0090] Group Flame retardant test results Minimum light transmittance (%) Bending radius Embodiment 27 qualified 66.0 17.0R Embodiment 28 qualified 64.4 17.2R Embodiment 29 qualified 70.5 17.5R Embodiment 30 qualified 68.1 17.2R Embodiment 31 qualified 65.5 17.0R Embodiment 32 qualified 67.9 17.1R Embodiment 33 qualified 64.2 16.8R Embodiment 34 qualified 68.3 17.3R Embodiment 35 qualified 67.9 17.5R Embodiment 36 qualified 69.2 17.0R Embodiment 37 qualified 69.8 16.7R Comparative Example 5 Failure 68.5 16.9R Comparative Example 6 Failure 68.2 17.3R Comparative Example 7 qualified 67.5 17.1R Comparative Example 8 qualified 60.3 17.5R Comparative Example 9 qualified 65.1 19.8R
[0091] The test results in Table 5 show that the flame retardant test results of the flexible cables manufactured in the examples are all qualified. The composite use of nitrogen flame retardants, zinc phytate and hexagonal boron nitride makes the cable have a good flame retardant effect. Comparative Examples 5 and 6 do not add nitrogen flame retardants and zinc phytate, and the flame retardant effect decreases. The low smoke performance test results show that the minimum transmittance is in the range of 60.3%-70.5%. Example 29 uses Mme and Dhe as nitrogen flame retardants, controls the ratio of cross-linked polyethylene powder and PDMS to 3:22, and the amounts of nitrogen flame retardant, zinc phytate and hexagonal boron nitride are 3, 4 and 1 parts respectively. The transmittance is 70.5%, and the low smoke performance is the best. By changing the amount of each component in the spinning solution, the bending radius of the obtained bending-resistant flexible cable is 16.7R-19.8R, and the bending resistance is good.
[0092] Embodiment 39
[0093] A bend-resistant flexible cable is manufactured according to the manufacturing method of Example 27, wherein the preparation method of the extruded fire-retardant filler is changed, as shown below: 110 parts of magnesium hydroxide and 11 parts of aluminum hydroxide are mixed, and then 220 parts of PDMS are added thereto. After stirring and mixing, the mixture is placed in a drying oven for drying to obtain a fire-retardant filler precursor; the fire-retardant filler precursor is ground to obtain an extruded fire-retardant filler with an average particle size of 400 nm.
[0094] Embodiment 40
[0095] The difference from Example 39 is that the amount of aluminum hydroxide is 15 parts.
[0096] Embodiment 41
[0097] The difference from Example 39 is that the amount of aluminum hydroxide is 18 parts.
[0098] Embodiment 42
[0099] The difference from Example 39 is that the amount of aluminum hydroxide is 20 parts.
[0100] Embodiment 43
[0101] The difference from Example 39 is that the amount of aluminum hydroxide is 15 parts.
[0102] Embodiment 44
[0103] The difference from Example 39 is that the extruded fire retardant filler is 350 nm.
[0104] Embodiment 45
[0105] The difference from Example 39 is that the extruded fire-retardant filler is 300 nm.
[0106] Embodiment 46
[0107] Different from Example 39, the extruded fireproof filler is 230nm.
[0108] Embodiment 47
[0109] The bending-resistant flexible cables prepared in Examples 39-46 were tested for fire resistance and halogen-free properties. The cables prepared in the present invention were 0.6 / 1kV cables. The fire resistance was tested using the method of GB / T 19216.21 "Line integrity test for cables or optical cables under flame conditions Part 1: Test method for cables with rated voltages of 0.6 / 1kV and below and outer diameters exceeding 20mm with fire and impact vibration at a flame temperature of not less than 830°C".
[0110] The halogen-free properties test adopts GB / T 17650.2-2021 "Test method for gases released during combustion of materials obtained from cables or optical cables Part 2: Determination of acidity (measured by pH) and conductivity", and the pH weighted value and conductivity weighted value are determined. The pH weighted value ≥4.3 is qualified, and the conductivity weighted value ≤10μs / mm is qualified.
[0111] The final test results are shown in Table 6.
[0112] Table 6 Fire resistance and halogen-free properties test results
[0113]
[0114]
[0115] The bending-resistant flexible cable prepared by the present invention has passed the fire resistance test, and the test results are all qualified, the 2A fuse is broken and the indicator light is not extinguished. Table 6 shows that the halogen-free flame-retardant extruded fireproof filler prepared according to Examples 39-46 of the present invention meets the requirements of the halogen-free test, and the pH weighted value and the conductivity weighted value both meet the standard test requirements, wherein the pH weighted value is 4.4-4.7, and the conductivity weighted value is 7.8-9.8μs / mm. In Examples 39-43, as the number of aluminum hydroxide portions changes, the conductivity weighted value shows a trend of first decreasing and then increasing, which meets the requirements of halogen-free properties. Comparison of the results of Examples 39 and 44-46 shows that as the particle size of the extruded fireproof filler decreases, the conductivity weighted value gradually decreases. The amount of aluminum hydroxide changes, and when the amounts of other components remain unchanged, the proportions of magnesium hydroxide, aluminum hydroxide and PDMS in the filler change, thereby affecting the conductivity weighted value. In summary, the bending-resistant flexible cable prepared by the present invention has good fire resistance and meets the requirements of the halogen-free property test.
[0116] Examples 48-53
[0117] Different from Example 1, the following manufacturing method is changed, as shown in Table 7.
[0118] Table 7 Manufacturing conditions of bending-resistant flexible cables
[0119]
[0120] Comparative Example 10
[0121] Instead of using corrugated copper tube sheath, WDZN-BYJ type low-smoke halogen-free sheath is used as the outermost structure.
[0122] Embodiment 54
[0123] The bending performance of the bending-resistant flexible cables prepared in Examples 48-53 and Comparative Examples 10 and 11 was tested, and the final results are shown in Table 7. The bending-resistant flexible cable structure manufactured by the present invention is as follows Figure 2 shown.
[0124] like Figure 2As shown, a bending-resistant flexible cable has the following structure, which is, from inside to outside, conductor material 1, composite insulating material 2, glass fiber 3, fireproof material 4, metal layer 5, extruded fireproof filler 6, and sheath 7. The cable of this structure obtained by the manufacturing method of the present invention has good bending resistance. Combined with the results of Table 7, the bending radius of the flexible cables prepared by Examples 48-53 of the present invention and Comparative Examples 10 and 11 is 11.5R-17.6R. Among them, in Examples 48 and 49, the conductor materials are selected from non-pressed annealed copper conductors and pressed annealed copper conductors, which have no obvious effect on the bending performance. The results of Examples 48, 50-53 show that by changing the type of alloy layer / metal layer, the bending resistance of the flexible cable changes, and the flexible cable manufactured by argon arc welding copper strip in Example 51 has the best bending resistance. Comparative Example 10 uses a flexible cable manufactured by a traditional WDZN-BYJ type low-smoke halogen-free sheath, and its bending performance is the best. Compared with Example 48, Comparative Example 11 does not use an annealing process, so the bending resistance of the flexible cable decreases.
[0125] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for manufacturing a bending-resistant flexible cable, characterized in that: The following steps are involved: Ultrasonicate the fibrillation suspension for 15-25 minutes to obtain an ultrasonic fibrillation suspension; In terms of the ratio of parts, muscovite flakes and muscovite powder are mixed with water at a ratio of 1-23:1-3, and ground for 13-20 minutes to obtain muscovite slurry; 0-10 parts of diisocyanate are added to the muscovite slurry to react to obtain modified muscovite slurry; 8-10 parts of the ultrasonic fiber precipitation suspension and the modified muscovite slurry are mixed and formed to obtain an aramid mica paper intermediate; coconut oil primary amine and silane epoxy resin are mixed at a ratio of 0.01-0.03:1 to obtain a mixture; the mixture is applied to the aramid mica paper intermediate to obtain a coating layer one; 0-50 parts of the ultrasonic fiber precipitation suspension and the modified muscovite slurry are mixed and formed, and then laminated with the aramid mica paper intermediate and the coating layer one to obtain two layers of composite aramid mica paper; The coating layer 2, the composite glass cloth and the two layers of composite aramid mica paper are laminated at 105-115° C. to obtain a composite insulating material; the coating thickness of the coating layer 1 and the coating layer 2 are both 0-30 μm; Cross-linked polyethylene powder and PDMS are mixed at a ratio of 1-3:9-97 to obtain a suspension; 0-4.5 parts of a nitrogen flame retardant, 0-4 parts of zinc phytate and 1-2 parts of hexagonal boron nitride are added to the suspension, stirred and mixed, and ultrasonicated to obtain a spinning solution; the spinning solution is spun to obtain a fireproof material; Mixing magnesium hydroxide, 11-20 parts of aluminum hydroxide and the PDMS, and grinding them to an average particle size of 230-400 nm to obtain an extruded fireproof filler; The bending-resistant flexible cable is manufactured by using the conductor material, the composite insulating material, the glass fiber, the fireproof material, the metal layer and the sheath.
2. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The amount of the ultrasonic fiber precipitation suspension in the second suspension is 30-50 parts.
3. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The diisocyanate is one of isophorone diisocyanate, 2,4-diisocyanate-1-methylcyclohexane, 1-isocyanato-2-(3-isocyanatopropyl)cyclohexane and 4-isocyanate-2-[(2-isocyanatecyclohexyl)methyl]-1-methylcyclohexane; and the amount of the diisocyanate used is 10 parts.
4. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The coating thickness of the coating layer 1 and the coating layer 2 are both 10-30 μm.
5. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The nitrogen flame retardant is one or two of N-cyano-N'-(hydroxymethyl)guanidine, a polymer of cyanoguanidine and N-(2-aminoethyl)-1,2-ethylenediamine, melamine, dicyandiamide and dodecylguanidine hydrochloride.
6. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The amount of the nitrogen flame retardant is 3-4.5 parts; the amount of the zinc phytate is 3-4 parts.
7. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The conductor material is one of a non-compacted annealed copper conductor, a compacted annealed copper conductor and a non-compacted copper conductor.
8. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The conductor material is coated with the composite insulating material; the glass fiber is filled outside the composite insulating material to obtain an insulating layer; the outside of the insulating layer is tightly wrapped with the fireproof material to obtain a fire-retardant belt; the outside of the fire-retardant belt is wrapped with the metal layer to obtain a metal belt; the extruded fireproof filler is filled; the sheath is used as the outermost layer to obtain the bending-resistant flexible cable; The metal layer is one of TU2H01 copper strip for interlocking armor, H65H02 copper strip for interlocking armor, argon arc welding copper strip, resistance welding copper strip, aluminum alloy strip for interlocking armor and cold press welding copper strip.
9. The method for manufacturing a bending-resistant flexible cable according to claim 1, characterized in that: The sheath is one of corrugated copper and WDZN-BYJ type low-smoke halogen-free sheath.
10. A bending-resistant flexible cable, characterized in that: The bending-resistant flexible cable comprises a conductor material, a composite insulating material, glass fiber, a fireproof material, a metal layer, an extruded fireproof filler and a sheath; the bending-resistant flexible cable is manufactured by the manufacturing method described in any one of claims 1 to 9; by changing the manufacturing method of the two-layer composite aramid mica paper, the breakdown time of the bending-resistant flexible cable is 14-20min, and the bending radius is 12.6R-19.4R; by changing the manufacturing method of the composite insulating material, the bending radius of the bending-resistant flexible cable is 13.8R-19.5R; by changing The manufacturing method of the fireproof material, the flame retardant test result of the bending-resistant flexible cable is qualified, the minimum light transmittance is 60.3%-70.5%, and the bending radius is 16.7R-19.8R; the manufacturing method of the extruded fireproof filler is changed, the fire resistance test result of the bending-resistant flexible cable is qualified, the pH weighted value is 4.4-4.7, and the conductivity weighted value is 7.8-9.8μs / mm; the types of the conductor material, the metal layer and the sheath are changed, and the bending radius of the bending-resistant flexible cable is 11.5R-17.6R.
